The NiFe Hydrogenases of the Tetrachloroethene-Respiring Epsilonproteobacterium Sulfurospirillum multivorans: Biochemical Studies and Transcription Analysis - Kruse, Stefan; Goris, Tobias; Wolf, Maria; Wei, Xi; Diekert, Gabriele (Frontiers in Microbiology, 2017)
The organohalide-respiring Epsilonproteobacterium Sulfurospirillum multivorans is able to grow with hydrogen as electron donor and with tetrachloroethene (PCE) as electron acceptor; PCE is reductively dechlorinated to cis-1,2-dichloroethene. Recently, a genomic survey revealed the presence of four gene clusters encoding NiFe hydrogenases in its genome, one of which is presumably periplasmic and membrane-bound, whereas the remaining three are cytoplasmic. To explore the role and regulation of the four hydrogenases, quantitative real-time PCR and biochemical studies were performed with S. multivorans cells grown under different growth conditions. The large subunit genes of the MBH and of a cytoplasmic group 4 hydrogenase, which is assumed to be membrane-associated, show high transcript levels under nearly all growth conditions tested, pointing towards a constitutive expression in S. multivorans. The genes encoding the large subunits of the other two hydrogenases were either not detected at all or only present at very low amounts. The presence of MBH under all growth conditions tested, even with oxygen as electron acceptor under microoxic conditions, indicates that MBH gene transcription is not regulated in contrast to other facultative hydrogen-oxidizing bacteria. The MBH showed quinone-reactivity and a characteristic UV/VIS spectrum implying a cytochrome b as membrane-integral subunit. Cell extracts of S. multivorans were subjected to native PAGE and hydrogen oxidizing activity was tested by native staining. Only one band was detected at about 270 kDa in the particulate fraction of the extracts, indicating that there is only one hydrogen-oxidizing enzyme present in S. multivorans. An enrichment of this enzyme and SDS PAGE revealed a subunit composition corresponding to that of the MBH. From these findings we conclude that the MBH is the electron-donating enzyme system in the PCE respiratory chain. The roles for the other three hydrogenases remain unproven. The group 4 hydrogenase might be involved in hydrogen production upon fermentative growth.